Enantioselective Synthesis of 4-Amino-3-hydroxybenzopyran Flavanol Derivatives from Chalcones - Gao, Qiwen; Xu, Lianyan L.; Parise, Vincent P.; Mehta, Yash R.; Aldrich, Leslie N. (Synthesis, 2018)
A concise method that is easily amenable for analogue synthesis has been developed to enantioselectively access 4-amino-3-hydroxybenzopyrans from chalcones. Epoxy alcohols were formed from chalcones through a Corey–Bakshi–Shibata reduction of the enone and subsequent Sharpless asymmetric epoxidation of the allylic alcohol. The epoxy alcohols were protected, regioselectively opened with various amines using catalytic europium(III) triflate, and the resulting free alcohols were orthogonally protected. Concomitant deprotection and intramolecular nucleophilic aromatic substitution provided the benzopyran core, which is poised to undergo additional reactions to provide a diverse chemical library with ideal properties for biological evaluation.
Keywords: natural products; stereoselective synthesis; medicinal chemistry; nucleophilic aromatic substitution; nitrogen; heterocycles